(untitled) (Research, Society and Development, 2022)
Through the investigation of areas at risk of mass sliding located in the city of Teófilo Otoni, three areas with intense erosive activity were identified, which were classified as gullies, being gullies 1 in the neighborhood Funcionários, gullies 2 in the neighborhood São João and gullies 3 in the neighborhood Vila Barreiros. Field visits were made to gather information about the origin of these phenomena, including the use of a drone. The characteristics of the city that directly influence the erosive processes were surveyed, such as: geology, relief, vegetation cover and use and occupation of the soil. The city of Teófilo Otoni presents intense vegetation suppression, which has exposed the soil to erosive agents, transforming the city into a place with a high predisposition for erosive processes. After the field analysis and the bibliographical survey, we came to the understanding that the first gully in the Funcionários neighborhood arose from a drainage project inadequately designed and poorly executed by the municipal government. The gully 2 in the São João neighborhood was aggravated by the construction of houses on the slope crest, which directed the rainfall flow to this location. The gully 3 in the Vila Barreiros neighborhood arose due to the construction of the city’s airport, which converged the surface runoff to the site of this phenomenon. The present article sought to explain how hydric and anthropogenic erosion were responsible for the increase in erosive processes with the consequent formation and aggravation of gullies in the city of Teófilo Otoni.